Penguatan Literasi Bimbingan dan Konseling di Sekolah Dasar bagi Wali Murid sebagai Strategi Kolaboratif Mendukung Perkembangan Anak Secara Holistik - Yuni Novitasari; Eko Susanto; Agus Wibowo; Satrio Budi Wibowo; Samson Fajar; Retno Fajarwati; Tri Octaria; Rayhana Esty Wulandari (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
Guidance and counseling in elementary schools play a crucial role in helping children understand themselves, adapt to their environment, develop learning skills, build healthy social relationships, and prevent more complex developmental problems. In practice, however, parents’ understanding of school guidance and counseling is often limited to the handling of problematic students. This condition may reduce the quality of collaboration between schools and families in supporting children’s development. This community service program aimed to improve parents’ literacy regarding the nature, functions, domains, services, and implementation of guidance and counseling in elementary schools. The program was conducted by a team of lecturers from department of Guidance and Counselling Universitas Muhamadiyah Metro for parents at SD Muhamadiyah Buya Hamka Metro. The implementation methods included partner needs identification, preparation of educational materials, interactive lectures, case discussions, parenting reflection, and participant understanding evaluation. The materials covered the definition of guidance and counseling, personal, social, learning, and career domains, as well as the functions of understanding, prevention, development, improvement, and system support through collaboration among classroom teachers, schools, parents, counselors, psychologists, and other relevant stakeholders. The results indicate that parents gained a more comprehensive understanding of guidance and counseling as a developmental service rather than merely a remedial service. Participants also demonstrated greater awareness of positive communication, learning assistance, character strengthening, early detection of children’s problems, and continuous collaboration with schools. This program contributed positively to building shared understanding between schools and families as a supportive ecosystem for the holistic development of elementary school children.